Author Correction: Thermally and field-driven mobility of emergent magnetic charges in square artificial spin ice - Morley, Sophie A.; Porro, Jose Maria; Hrabec, Aleš; Rosamond, Mark C.; Venero, Diego Alba; Linfield, Edmund H.; Burnell, Gavin; Im, Mi-Young; Fischer, Peter; Langridge, Sean; Marrows, Christopher H. (Scientific reports, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.An amendment to this paper has been published and can be accessed via a link at the top of the paper.